Strategi Mengendalikan Turnover Karyawan: Studi Kasus Pada Sebuah Rumah Sakit Swasta Di Kota Manado - Tigau, Felania Injilia; Sugiarto, Agus (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2022)
This study aimed to determine the hospital's strategy for controlling turnover. The increasing turnover nowadays has become a severe problem for many companies. The turnover phenomenon becomes a problem for companies when employees who have high achievements leave the company. Hospitals have the opportunity to get negative and positive effects due to turnover. The unit of observation in this study is the largest private hospital in the city of Manado. The hospital has succeeded in lowering the employee turnover rate in recent years. The method used in this research is a qualitative case study. Data collection was carried out by in-depth interviews, observation, and documentation. The results showed that the strategies used by hospitals in controlling turnover were recognizing employees as assets, creating employee engagement, and paying attention to competitors.